1988
DOI: 10.1080/02566702.1988.9648146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the intensity and phenophase of defoliation and water stress on the rate of photosynthesis and the recovery of carbohydrate reserves inacacia karroohayne

Abstract: To cite this article: W.R. Teague (1988) Effect of the intensity and phenophase of defoliation and water stress on the rate of photosynthesis and the recovery of carbohydrate reserves in acacia karroo hayne, Journal of the Grassland Society of Southern Africa, 5:4, 223-226, ABSTRACTA field study was conducted with Acacia karroo plants to determine changes in relative photosynthetic rates, the extent of carbohydrate reserve depletion and the rate reserves take to recover, following defoliation by goats at diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Of all the treatment interactions, wherever the seedlings were subjected to grass competition, they were suppressed irrespective of increased moisture and nitrogen fertilization. The results are consistent with the findings from other studies, which showed that grass competition significantly reduces the growth of A. karroo seedlings (Teague, 1988, 1992; Chirara, 2001). Irrigation significantly interacted with grass competition and the mean stem length of nonirrigated A. karroo seedlings was higher than the irrigated ones.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Of all the treatment interactions, wherever the seedlings were subjected to grass competition, they were suppressed irrespective of increased moisture and nitrogen fertilization. The results are consistent with the findings from other studies, which showed that grass competition significantly reduces the growth of A. karroo seedlings (Teague, 1988, 1992; Chirara, 2001). Irrigation significantly interacted with grass competition and the mean stem length of nonirrigated A. karroo seedlings was higher than the irrigated ones.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study showed that the irrigated seedlings had better growth performance, irrespective of other factors with which irrigation interacted. Similar experiments have also indicated that A. karroo seedlings are sensitive to moisture, and thus require adequate water to grow and become successfully established (Teague, 1988, 1992; O’connor, 1994; Chirara, 2001). The results of this study are also consistent with the nonequilibrium model proposed by Higgins, Bond & Trollope (2000), which states that the recruitment of woody plants in savannas is controlled by rainfall.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Interestingly, Du Toit et al (1990) found that the chemical defences of A. nigrescens were lower near waterholes than at control sites. This result was related to obvious differences in browsing levels, but could also be a consequence of differences in regrowth capacity that is dependent on the availability of water (but see also Teague 1988). Further research is required on the effect of variations in water supply on plant defences.…”
Section: Plant-animal Interactions In Desert Environmentsmentioning
confidence: 97%